Current Status of Primary, Secondary, and Tertiary Prevention of Coronary Artery Disease - Prasad, Kailash (International Journal of Angiology, 2021)
Fifty percent of all death from cardiovascular diseases is due to coronary artery disease (CAD). This is avoidable if early identification is made. Preventive health care has a major role in the fight against CAD. Atherosclerosis and atherosclerotic plaque rupture are involved in the development of CAD. Modifiable risk factors for CAD are dyslipidemia, diabetes, hypertension, cigarette smoking, obesity, chronic renal disease, chronic infection, high C-reactive protein, and hyperhomocysteinemia. CAD can be prevented by modification of risk factors. This paper defines the primary, secondary, and tertiary prevention of CAD. It discusses the mechanism of risk factor–induced atherosclerosis. This paper describes the CAD risk score and its use in the selection of individuals for primary prevention of CAD. Guidelines for primary, secondary, and tertiary prevention of CAD have been described. Modification of risk factors and use of guidelines for prevention of CAD would prevent, regress, and slow down the progression of CAD, improve the quality of life of patient, and reduce the health care cost.
Keywords: atherosclerosis; coronary artery disease; modifiable risk factors of CAD; guidelines for prevention; primary prevention; secondary prevention; tertiary prevention; quality of life